2022
DOI: 10.1038/s41467-022-33996-1
|View full text |Cite
|
Sign up to set email alerts
|

Divergent regioselective Heck-type reaction of unactivated alkenes and N-fluoro-sulfonamides

Abstract: The control of regioselectivity in Heck-type reaction of unactivated alkenes represents a longstanding challenge due to several detachable hydrogens in β–H elimination step, which generally afford either one specific regioisomer or a mixture. Herein, a copper-catalyzed intermolecular Heck-type reaction of unactivated alkenes and N-fluoro-sulfonamides with divergent regioselectivities is reported. The complete switch of regioselectivity mainly depends on the choice of different additives. Employment of alcohol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“…Spin crossover through an MECP from triplet Int-179 to singlet reductive elimination transition state TS-180 has a free energy barrier of 7.9 kcal/mol (Figure b). A recent study reported by Fu, Guan, and co-workers suggested that a similar reductive elimination ( TS-186 ; Figure b) is also operative in the C–N bond formation of alkyl radical and amide anion, affording a four-membered lactam …”
Section: Copper-mediated Radical Transformations Via Reductive Elimin...mentioning
confidence: 75%
See 1 more Smart Citation
“…Spin crossover through an MECP from triplet Int-179 to singlet reductive elimination transition state TS-180 has a free energy barrier of 7.9 kcal/mol (Figure b). A recent study reported by Fu, Guan, and co-workers suggested that a similar reductive elimination ( TS-186 ; Figure b) is also operative in the C–N bond formation of alkyl radical and amide anion, affording a four-membered lactam …”
Section: Copper-mediated Radical Transformations Via Reductive Elimin...mentioning
confidence: 75%
“…A recent study reported by Fu, Guan, and co-workers suggested that a similar reductive elimination (TS-186; Figure 27b) is also operative in the C−N bond formation of alkyl radical and amide anion, affording a four-membered lactam. 92 4.3. C−O Bond Formation.…”
Section: C−n Bond Formationmentioning
confidence: 99%
“…When employing allylic sulfides as substrates, the challenging 1,2-insertion occurred to afford the Int. I with a locked conformation, wherein β–H elimination was suppressed. Conversely, when homoallylic sulfides are employed, the 2,1-insertion takes place, giving rise to Int.…”
Section: Resultsmentioning
confidence: 99%
“…1b). Upon treatment with transition metal (Fe, Cu, Ni) or photocatalysis, the N-fluoroamides can undergo N-F reduction via single-electron transfer (SET) followed by Hofmann-Löffler-Freytag (HLF) type hydrogen atom transfer (HAT) to induce remote C(sp 3 )-H functionalization [70][71][72][73][74][75][76][77][78][79][80] or intramolecular cyclization 81 . Recently, Nagib and co-workers reported a dual photoredox-and copper-catalyzed remote C-H desaturation of N-fluoroamides to furnish δ vinyl amides, that could be converted to diverse families of medicinal motifs 82 .…”
mentioning
confidence: 99%